A review of the hot spot analysis and the research status of single-atom catalysis based on the bibliometric analysis. (17th February 2021) - Xing, Yi; Guo, Zefeng; Su, Wei; Wen, Wei; Wang, Xiaona; Zhang, Hui
Abstract : The bibliometric method was used to analyze the development trend and research hotspots in past 10 years since the concept of single-atom catalysis was proposed in 2011. This article can provide some guidance for future research of SACs. Abstract : Single-atom catalysis is a new field that has developed rapidly in recent years and has greatly helped the development of catalytic science. We have processed a large amount of literature data through the Web of Science database. The bibliometric method was used to analyze the development trend and research hotspots over the past 10 years since the concept of single-atom catalysis was proposed in 2011. Results show that the field of single-atom catalysis is currently at a high-speed development stage. China is in a leading position in terms of comprehensive strength, with the largest number of publications and great influence. Most productive journals and institutions are ACS Catalysis and Chinese Acad. Sci. Single-atom catalysis has the most research results in the field of chemistry. In addition, the most commonly used keywords are "density functional theory", "oxygen reduction reaction", "electrocatalysis", "co oxidation", "graphene", "heterogeneous catalysis", "platinum", "hydrogen evolution reaction", which reflect the research direction of the current field. This article reviews the main research content of single-atom catalysts in order to facilitate researchers understanding the current situation in the field, and to also provide some guidance for future research.